Electrophoretic deposition of polyetheretherketone/polytetrafluoroethylene on 316L SS with improved tribological and corrosion properties for biomedical applications - Imran, Ayman; Malik , Rizwan Ahmed; Alrobei, Hussein; Ur Rehman, Muhammad Atiq (Frontiers in Materials, 2024)
316L stainless steel (316L SS) has poor wear and corrosion resistance compared to that of the Cp-Ti and Ti-6Al-4V implants (when studied under a physiological environment using phosphate-buffered saline (PBS)). However, 316L SS implants are cost-effective. Their wear and corrosion properties can be improved by depositing biocompatible coatings. In this research work, a polymer coating of polyetheretherketone (PEEK) and polytetrafluoroethylene (PTFE) was deposited at optimized parameters (20 V with 3 min) on 316L SS by electrophoretic deposition (EPD). In this study, we compared the performance between PEEK coating and hybrid PEEK/PTFE coatings for biomedical applications. The PEEK/PTFE coating was sintered at 350 °C for 30 min. Scanning electron microscopy (SEM) analysis revealed that PEEK/PTFE coating showed uniform coating with a uniform thickness of ~80 µm. Fourier Transform Infrared (FTIR) spectroscopy analysis confirmed the presence of bonds attributed to the PEEK and PTFE coating. PEEK/PTFE coating exhibited adequate average surface roughness (Ra) 2.1 ± 0.2 µm with a high value of contact angle 132.71 ± 3 indicating the hydrophobic nature of PEEK/PTFE coating. Scratch test evaluated that PEEK/PTFE coating demonstrated a 7 N load which indicated the good adhesion of the coating with 316L SS. Furthermore, PEEK/PTFE coating demonstrated good wear resistance, capable of withstanding a 7 N load under dry conditions showed a specific wear rate of ~ 0.0114 mm 3 /Nm. Electrochemical analysis conducted in phosphate-buffered saline (PBS) solution demonstrated that the corrosion rate of 316L SS was reduced from 0.9431 mpy to 0.0147 mpy by depositing PEEK/PTFE coating. Thus, the developed coatings presented suitable to wear and corrosion resistance to be considered for potential orthopedic application.